Geopolitical image of Russia: a view from Siberia - Litvinova, Tatyana N.; Vinokurova, Anna V. (The New Research of Tuva, 2013)
Review to: Yerokhina E.A. Siberian vector of Russian domestic geopolitics. Novosibirsk, 2012. 418 p.
Keywords: gepolitika; review; edition-2012; Siberia; Russia